Growth Response And Results On Peanut Some Variety Against Of Palm Bunch Ash in Alluvial Soil - Oskar Hendrianus; Surachman .; Setia Budi (Jurnal Sains Pertanian Equator, 2019)
The aim of this research is to find out the best variety and dose of palm bunch ash on peanut on alluvial soil, and to know whether there is interection between variety and dosage of palm bunch ash on peanut on alluvial soil. This study used Split Plot Design with two treatment factors consisting of variety (V) as main plot and palm bunch ash (A) as subplot. The variety consist of three levels, namely : v1 = (jerapah), v2 = (talam 2) and v3 = (talam 3) and palm bunch ash consist of three levels, namely : a1 = ( 1,5 ton/ha), a2 = ( 3 ton/ha) and a3 = ( 4,5 ton/ha). Each of the treatment was repeated 3 times. The observed variables in this study are plant height (cm), root volume (cm3), the dry weight of the plant (g), the number of pods per plant, the dry weight of kernel per plant (g) and dry weight of kernel per plot. The results showed that the using of jerapah variety and 3 ton/ha dose of palm bunch ash is best average are the number of pods per plant (pod), the dry weight of kernel per plant (g) and dry weight of kernel per plot (g) . But there is no interaction between variety and palm bunch ash on the growth and nyield of peanut on alluvial soil. Key word : variety, peanut, palm bunch ash, alluvial soil.